Update on Evaluation, Prevention, and Management of Postpartum Hemorrhage. Issue 2 (March 2018) - Simpson, Kathleen Rice
Abstract : The American College of Obstetricians and Gynecologists has updated their guidelines on postpartum hemorrhage. Review the October 2017 practice bulletin and work with the multidisciplinary team on your unit to adopt the recommendations to promote patient safety.